New Brunswick and Nova Scotia:: the First Geological Field Trip by a North American College - Falcon-Lang, Howard (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2009)
ABSTRACT The first known geological excursion by a North American college was conducted in 1835. Twenty staff and students belonging to Williams College — a liberal arts college in Massachusetts, USA — explored the geology bordering the Bay of Fundy in northeast Maine, New Brunswick and Nova Scotia. Led by two young professors of natural history, Ebenezer Emmons and Albert Hopkins, the party made extensive observations around Pasammaquoddy Bay, Saint John, Parrsboro, and Windsor, as well as more widely through the Minas and Cumberland basins. Although partly following in the footsteps of two pioneering Bostonians, Charles Jackson and Francis Alger, who had reconnoitred the region in the late 1820s, the Williams College party nevertheless made several original observations. One of most important was a study of the anatomy and paleoclimatic significance of permineralized plants from Joggins and Grindstone Island undertaken by Emmons. This was only the second study of its kind worldwide and later inspired William Dawson to do similar work. Largely overlooked by historians of geology, the Williams College expedition, which comprised a four-week voyage of about 1800 km, illustrates well the challenges and opportunities of geological field work in the early Nineteenth Century.